BENTUK DAN SUSUNAN GERAK TARI BARIS - Ni Nyoman Wati (Greget, 2021)
Dance is a cultural art treasure that always appears alive and growing in every region in Indonesia and even the world as a reflection of their respective cultural arts. Bali is one of the regions in Indonesia that has a variety of arts and culture, one of which is dance. It is certain that other regions and several places in the world keep their respective arts and cultures in different forms, forms, functions and meanings. Baris dance as one of the Balinese dance repertoires is used as a topic in this article which will focus on Baris which depicts the spirit of warriors. In Bali there are several types of Baris dance that are intended to complement ritual ceremonies. The Baris Dance, which will be described in this article, is a casual dance that is commonly used for entertainment in various non-ritual performances.